Enhancing the Competence of Supreme Court Judges Through the Specialization of Judges at the Supreme Court - Mustakim; Syafrida, Syafrida; Warsito; Masidin (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
The research aims to analyze the characteristics of judicial reviews carried out by the Supreme Court and efforts to increase the competence of Supreme Court judges through differentiation of judges' expertise in judicial reviews. This research is normative legal research with a conceptual and statutory approach. The results of the research show that the characteristics of the judicial review carried out by the Supreme Court are extensive or broad in nature, not only focusing on and referring to the hierarchy of statutory regulations, but the Supreme Court must first qualify a statutory regulation that is formed based on authority or on the orders of higher statutory regulations. The means to increase the competence of Supreme Court judges through differentiation of judges' expertise in judicial review are necessary so that judges' considerations can be comprehensive and substantive. Differentiation of expertise of Supreme Court judges is oriented towards aspects of special training for judges related to judicial review at the Supreme Court because the characteristics of judicial reviews are testing general and abstract norms, and further differentiation of judges' expertise needs to be optimized in terms of the types and characteristics of the regulations being tested.